Dream Poems. The Surreal Conditions of Modernism - Louise Mønster (Humanities, 2018)
The article discusses three Swedish dream poems: Artur Lundkvist’s “Om natten älskar jag någon…„ from Nattens broar (1936), Gunnar Ekelöf’s “Monolog med dess hustru„ from Strountes (1955), and Tomas Tranströmer’s “Drömseminarium„ from Det vilda torget (1983). These authors and their poems all relate to European Surrealism. However, they do not only support the fundamental ideas of the Surrealist movement, they also represent reservations about, and corrections to, this movement. The article illuminates different aspects of dream poems and discusses the status of this poetic genre and its relation to Surrealism throughout the twentieth century.